Genome Sequence of Pseudomonas putida Strain SJTE-1, a Bacterium Capable of Degrading Estrogens and Persistent Organic Pollutants - Liang, Rubing (American Society for Microbiology, 2012)
Pseudomonas putida strain SJTE-1 can utilize 17β-estradiol and other environmental estrogens/toxicants, such as estrone, and naphthalene as sole carbon sources. We report the draft genome sequence of strain SJTE-1 (5,551,505 bp, with a GC content of 62.25%) and major findings from its annotation, which could provide insights into its biodegradation mechanisms.